Pengembangan Desa Wisata dalam Menjamin Tourism Sustainable di Desa Kubu Gadang Kota Padang Panjang - Feronia Mayliana; Jumiati Jumiati (Jurusan Ilmu Administrasi Negara, 2023)
This research aims to determine the development of Tourism Villages in Guaranteeing Sustainable Tourism in Kubu Gadang Village, Padang Panjang City. This research was conducted using a qualitative approach with a descriptive method, in determining informants the researcher used a purposive sampling method. Data collection techniques are carried out using interviews, observation and documentation. In testing the validity of the data, researchers used source triangulation and method triangulation. Meanwhile, data analysis techniques use data reduction techniques, data presentation, and drawing conclusions/verification. From the research results, it can be seen that the Kubu Gadang tourist village has carried out tourism development through several components such as tourist attractions, accessibility, amenities and additional services. Sustainable tourism in the Kubu Gadang tourist village, seen from an economic aspect, plays a very good role in improving the economy of the local community; the environmental aspect has the potential for rice fields with mountain views to create opportunities for tourism activities; and the social aspect makes social relations strong, maintains culture through tour packages related to the customs found in the Kubu Gadang tourist village. However, in the process of developing the Kubu Gadang tourist village in ensuring sustainable tourism, there are obstacles, namely internal obstacles, namely (a) not all of the human resources or tourist village managers have passion in their respective fields; (b) the Kubu Gadang tourist village facilities are inadequate and the maintenance of the facilities has not been maintained; (c) the budget for developing the Kubu Gadang tourist village is inadequate. Meanwhile, external constraints are (a) environmental conditions around the Kubu Gadang tourist village, Padang Panjang City; (b) there is no regulation. Efforts that can be made to overcome obstacles to the development of the Kubu Gadang Tourism Village, Padang Panjang City in ensuring sustainable tourism are (a) involving managers of the Kubu Gadang tourist village who do not have passion in their field and have not mastered their work and main duties and functions through training; (b) the management of the Kubu Gadang tourist village openly accepts anyone who wants to join as a tourist village activist; (c) establishing a sharia tourism cooperative and selling tour packages to meet the budget for developing the Kubu Gadang tourist village; (d) conducting outreach regarding the importance of maintaining cleanliness to the people of Kubu Gadang and tourists; (e) carry out tree planting programs and reduce the use of plastic.